2012
DOI: 10.1093/molbev/mss066
|View full text |Cite
|
Sign up to set email alerts
|

Microevolution of Cryptococcus neoformans Driven by Massive Tandem Gene Amplification

Abstract: The subtelomeric regions of organisms ranging from protists to fungi undergo a much higher rate of rearrangement than is observed in the rest of the genome. While characterizing these ~40-kb regions of the human fungal pathogen Cryptococcus neoformans, we have identified a recent gene amplification event near the right telomere of chromosome 3 that involves a gene encoding an arsenite efflux transporter (ARR3). The 3,177-bp amplicon exists in a tandem array of 2-15 copies and is present exclusively in strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 82 publications
0
49
0
Order By: Relevance
“…C. neoformans telomeres are very different to those seen in brewing yeast as they are not gene-poor, and there has been no reported evidence of silencing46. Consistent with this, Sir2 does not interact with the telomeric regions in this pathogen; the closest binding sites in the ChIP-seq data were a minimum of ~29 kb away from the ends of the chromosomes.…”
Section: Resultsmentioning
confidence: 69%
“…C. neoformans telomeres are very different to those seen in brewing yeast as they are not gene-poor, and there has been no reported evidence of silencing46. Consistent with this, Sir2 does not interact with the telomeric regions in this pathogen; the closest binding sites in the ChIP-seq data were a minimum of ~29 kb away from the ends of the chromosomes.…”
Section: Resultsmentioning
confidence: 69%
“…By generating modification-specific antibodies, we found that H3K27me3 is deposited by the EZH2/E(z) ortholog across subtelomeric domains that repress the expression of underlying genes and noncoding transcripts. Polycomb heterochromatin may therefore have a specialized role in the regulation of subtelomeres, which in fungi are enriched for rapidly-evolving genes involved in niche adaptation and specialized metabolic functions (Brown et al, 2010; Chow et al, 2012). Consistent with this idea, the 41 kb average size of subtelomeric H3K27me3 domains closely matches a computational prediction of C. neoformans subtelomere size based on enrichment for metabolism-related gene products (~40 kb) (Chow et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Polycomb heterochromatin may therefore have a specialized role in the regulation of subtelomeres, which in fungi are enriched for rapidly-evolving genes involved in niche adaptation and specialized metabolic functions (Brown et al, 2010; Chow et al, 2012). Consistent with this idea, the 41 kb average size of subtelomeric H3K27me3 domains closely matches a computational prediction of C. neoformans subtelomere size based on enrichment for metabolism-related gene products (~40 kb) (Chow et al, 2012). Intriguingly, subtelomeric genes in other pathogenic fungi are silenced by domains of repressive chromatin and respond to environmental changes during the process of host infection, raising the possibility that Polycomb heterochromatin could contribute to the pathogenicity of C. neoformans (Domergue et al, 2005; Las Peñas et al, 2003; McDonagh et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…They can confer a quantitative advantage in situations in which having larger amounts of the corresponding protein is advantageous. Examples of such coding-gene duplications abound for proteins involved in functions directly related to the environment (e.g., resistance to xenobiotics through higher levels of detoxification, [68]; greater amylase production providing adaptation to a starch-rich diet in humans and dogs, [9,10]; higher hexose transporter levels for adaptation to an environment in which resources are limited, [11]). However, homogeneous duplications are also often associated with deleterious pleiotropic effects (or selective costs), probably due to the disruption of biochemical balance or overproduction costs ([12], e.g., in Culex pipiens , esterases may account for up to 12% of total protein, by weight, [13]).…”
Section: Introductionmentioning
confidence: 99%